2015
DOI: 10.1016/j.tet.2015.04.097
|View full text |Cite
|
Sign up to set email alerts
|

Lead structures for applications in photodynamic therapy 7. Efficient synthesis of amphiphilic glycosylated lipid porphyrin derivatives: refining linker conjugation for potential PDT applications

Abstract: Leave this area blank for abstract info.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…One potential structure that opens avenues to these types of arrays is triptycene. By drawing from extensive work previously invested in selective microwave assisted “click“ chemistry20c previously conducted in our group, similar success was anticipated for triptycene.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…One potential structure that opens avenues to these types of arrays is triptycene. By drawing from extensive work previously invested in selective microwave assisted “click“ chemistry20c previously conducted in our group, similar success was anticipated for triptycene.…”
Section: Resultsmentioning
confidence: 72%
“…As a proof of concept the preparation of mesogenic triptycene derivatives were investigated by 1,3‐dipolar cycloaddition reaction of 1‐azidoalkane to trialkyne system 20 similar to those previously prepared by Suzuki coupling (Scheme ). By implementing similar reaction conditions as previously reported for glycosylated porphyrin derivatives within our group,20c,20d threefold 1,3‐dipolar cycloaddition reaction of triptycene 20 was achieved in 89 % yield by microwave‐assisted conditions with 1‐azidononane in the presence of [Cu(CH 3 CN) 4 ][PF 6 ] (0.35 equiv.) in degassed dimethylformamide (DMF; 8 mL) at 115 °C for 30 min.…”
Section: Resultsmentioning
confidence: 90%
“…Since the double bond confers a certain degree of rigidity that influences the self-assembly of the corresponding functional material, the catalytic hydrogenation step was performed before the reaction with 3-azidopropylamine affording derivative 16 with a good yield (>60%) [41]. Senge and co-workers used the bis(4-ethynylphenyl)porphyrin derivative P56 to prepare amphiphilic target molecules P58 to be used in PDT (Scheme 18) [42]. In this study, the authors used the 3-azidopropyl α-d-mannopyranoside as the carbohydrate component.…”
Section: Carbohydrate-porphyrin Conjugatesmentioning
confidence: 99%
“…The possibility to easily modify the macrocycle at different loci, alterations of macrocyclic aromatic system, coordination of different metal ions and other chemical alterations also explains their extensive use in PDT. 25,26,27,28,29,30 Notably, these macrocycles can absorb in the spectral range of 600-850 nm, allowing for excellent light tissue penetration. Yet, only a limited number of PSs have been used in clinical studies and found approval from the regulatory bodies.…”
Section: Photosensitizers In Pdtmentioning
confidence: 99%
“…78 Chlorin e 6 (56), a chlorophyll-derived tetrapyrrole, combined with the cationic polymer polyethylenimine (PEI) also showed PACT efficiency against some strains of Gram-negative bacteria. 79 Indeed, PSs possessing a positively charged molecular structure, such as tetracationic porphyrins, phthalocyanines and dyes such as toluidine blue O (31) or methylene blue (30), are the most suited to eliminate tough Gram-negative species of bacteria. The latter, in contrast to Gram-positive bacteria, are impermeable to many anionic and lipophilic molecules.…”
Section: Cancer Therapymentioning
confidence: 99%